2021
DOI: 10.1016/j.xjtc.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Complete percutaneous decannulation from femoral venoarterial extracorporeal membrane oxygenation

Abstract: Objectives: To evaluate the clinical outcomes and perioperative complications associated with complete percutaneous decannulation of femoral venoarterial extracorporeal membrane oxygenation (VA-ECMO) with the MANTA closure device.Methods: This is a retrospective analysis of a single surgeon consecutive series of 14 patients at a single center who underwent decannulation from VA-ECMO, 10 of whom underwent a percutaneous method of femoral cannula removal.Results: After a mean duration of VA-ECMO support of 7.4 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(54 citation statements)
references
References 14 publications
0
54
0
Order By: Relevance
“…However, these techniques have not yet demonstrated improvements in clinical outcomes compared with surgical removal in this setting. [4][5][6][7][8] We suspect postclosure compared with preclosure may result in a more technically challenging VA-ECMO decannulation procedure and be prone to excessive blood loss when attempting to deploy the suture device after large-bore arterial access such as provided with VA-ECMO. It has been suggested that a possible…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these techniques have not yet demonstrated improvements in clinical outcomes compared with surgical removal in this setting. [4][5][6][7][8] We suspect postclosure compared with preclosure may result in a more technically challenging VA-ECMO decannulation procedure and be prone to excessive blood loss when attempting to deploy the suture device after large-bore arterial access such as provided with VA-ECMO. It has been suggested that a possible…”
Section: Discussionmentioning
confidence: 99%
“…However, these techniques have not yet demonstrated improvements in clinical outcomes compared with surgical removal in this setting. 4 , 5 , 6 , 7 , 8 We suspect postclosure compared with preclosure may result in a more technically challenging VA-ECMO decannulation procedure and be prone to excessive blood loss when attempting to deploy the suture device after large-bore arterial access such as provided with VA-ECMO. It has been suggested that a possible advantage of the postclosure technique compared with preclosure in VA-ECMO is that, given the uncertain duration of extracorporeal therapy, suture-mediated system stitches may remain in place and be subject to infection for prolonged periods of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The University of Maryland Medical Center Extracorporeal Membrane Oxygenation (ECMO) group is to be congratulated for their innovation in tackling one of the most annoying problems encountered in the patient with cardiopulmonary failure. 1 At the risk of ignoring the insights from Tversky and Kahneman in their 1971 manuscript on “Belief in the Law of Small Numbers,” 2 I would propose that deploying the MANTA (Teleflex, Morrisville, NC) in the ex post management of percutaneous cannulation represents a promising strategy for future study. As we celebrate the use of this beautiful new mouse trap, I think it is important to consider the question of how we found ourselves with a rodent infestation in the first place.…”
mentioning
confidence: 99%
“…In this issue of the Journal , Shah and colleagues 1 from University of Maryland report on their retrospective observational experience with decannulation of extracorporeal membrane oxygenation (ECMO) support using the MANTA large-bore vascular closure device. The study details their experience with 10 consecutive patients who underwent decannulation using the device.…”
mentioning
confidence: 99%